Measurements of Air Ion Concentrations and Electric Field Strengths for HVDC Applications - Mikiver, Anders (My University, 2017)
High Voltage Direct Current (HVDC) enables transfer of electric power over long distances with high efficiency. In order to further increase the efficiency, the voltage levels are increasing. In turn, this means that for the design of both robust and cost effective electric insulation, the importance of understanding specific DC voltage related phenomena also increase. For this thesis, specific DC voltage phenomena were studied by means of simultaneous measurements of air ion concentrations, DC electric field strength and ion current. The measurements were performed at ABB Corporate Research in Västerås from January to May of 2017, utilizing a data acquisition system denoted the ion box. Measurements both with and without applied voltage were carried out. The measurements without voltage were implemented in order to observe how the equilibrium ion concentrations varied with respect to location, and with other parameters such as humidity. The high voltage measurements were performed with different voltage polarities and electrode configurations, resulting in different electric field distributions. Additionally, the level of humidity was also varied during the high voltage measurements. The results of the measurements demonstrate that equilibrium ion concentration correlates strongly with concentrations of radon. In turn, the concentrations of both ions and radon were strongly affected by the air ventilation system for the indoor measurements. Furthermore, due to the tendency of radon gas to accumulate indoors, the measured indoor ion concentrations were larger than the ion concentrations outdoors. From the high voltage measurements the different regions of the general current-voltage characteristics for air were observed. The measurements also confirm that positive corona results in the injection of positive ions, whereas negative corona injects negative ions. In turn, the corona injected ions are shown to disrupt the linear relationship between applied DC voltage and DC electric field strength.
Keywords: Energi; Grundläggande vetenskaper; Elektrofysik; Elkraftteknik; Energy; Basic Sciences; Electrophysics; Electric power engineering